ISLAM AND PLURALISM: A Religious-Sociologic Analysis on the Role of Indonesian Muslims in Strengthening Social Integration - Abdullah Idi (Asia-Pacific Journal on Religion and Society, 2022)
It appears that the threat or problem of social and national disintegration is an integral part of the process of Indonesian national history. Since 1997, Indonesia still faces various social crises such as corruption, poverty, low or education backwardness, unemployment, crime, illegal logging, ethnic and community problems, religious conflicts and separatism. As a result, these conditions have led to a declining sense of nationalism which then increases the potential for social and national disintegration. For example, when President Susilo Bambang Yudhoyono visited Ambon some time ago, we were shocked by the Peak Lele dance performed by supporters of the RMS movement in Ambon. GAM supporters then formed a local political party called the Free Aceh Movement Party. Supporters of the Organization for a Free Papua (OPM) raise the Morning Star flag to signal the existence of the Free Papua Movement. Therefore, all elements of the Indonesian nation should take responsibility and play an active role in strengthening the unity of this nation. Like other elements of the nation, Indonesian Muslims, as the country's majority, are also responsible and must play an active role in strengthening the country's unity and integrity. On this topic, this article focuses on a conceptual analysis of the relationship between Islam and pluralism, and then elaborates on the extent to which Indonesian Muslims play a role in promoting social and ethnic integration in a pluralistic Indonesian society.